2013
DOI: 10.1021/ac303008f
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Nucleic Acid Enhanced FO-SPR DNA Melting for Detection of Mutations inLegionella pneumophila

Abstract: A home-built fiber optic surface plasmon resonance platform (FO-SPR) was applied to directly screen PCR amplified DNA for mutations. The FO-SPR sensor was used for real-time monitoring of DNA duplex melting during high resolution temperature cycling. The signal of the DNA melting was enhanced by means of gold nanoparticle labels. This FO-SPR genetic assay allowed for detection of single-point mutations (SNP) in less than 20 min. The concept was demonstrated for the analysis of 9 different serogroups of the bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Recent studies have shown HRM analysis to be a powerful technique for characterizing antibiotic resistance and typing respiratory disease agents, including M. pneumoniae, C. pneumoniae, and Chlamydophila psittaci (453)(454)(455)(456)(457)(458)(459). To our knowledge, HRM analysis for intraspecies or interspecies Legionella discrimination has been included in only a few studies (460)(461)(462)(463); however, this approach seems promising for future Legionella diagnostics or typing.…”
Section: Emerging Methods and Technologiesmentioning
confidence: 99%
“…Recent studies have shown HRM analysis to be a powerful technique for characterizing antibiotic resistance and typing respiratory disease agents, including M. pneumoniae, C. pneumoniae, and Chlamydophila psittaci (453)(454)(455)(456)(457)(458)(459). To our knowledge, HRM analysis for intraspecies or interspecies Legionella discrimination has been included in only a few studies (460)(461)(462)(463); however, this approach seems promising for future Legionella diagnostics or typing.…”
Section: Emerging Methods and Technologiesmentioning
confidence: 99%
“…Standard optical fibers have emerged over the years as excellent alternatives that can compete with the sensitivity and specificity of prism-based SPR sensors, while offering the advantage of low cost and small size greatly desired for developing a POC tool. One such platform, namely fiber optic surface plasmon resonance (FO-SPR), has been previously described by our group as a promising biosensor for protein-and DNA-based assays (Delport et al 2012;Janssen et al 2012;Knez et al 2013;Knez et al 2014;Pollet et al 2011;Pollet et al 2009;Tran et al 2011). The FO-SPR biosensor makes use of multimode optical fibers that facilitate SPR generation and enable implementation of bioassays.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, coupling SPR to fiber optic (FO) technology triggered notable advancements in the field, by offering attractive advantages over the classical prism-based SPR platforms, such as simplicity, portability, cost-effectiveness and miniaturization [2]. FO-SPR sensors were successfully used already in a variety of applications, such as screening for bacterial infections [3], monitoring of environmental water pollution [4] or checking for specific toxins [5] and allergens [6] in food, among others. However, their performance still needs to be improved in order to match traditional prismbased SPR sensors, and consequently, to switch from laboratory proofs-of-principle to commercial products.…”
Section: Introductionmentioning
confidence: 99%